1997
DOI: 10.1086/310690
|View full text |Cite
|
Sign up to set email alerts
|

The Accreting White Dwarf in the Close Binary EUVE J1016−053

Abstract: The hot white dwarf in the close binary EUVE J1016Ϫ053 (ϭRE 1016Ϫ053) has been classified as a DAO white dwarf; its mixed H͞He composition has been attributed to steady accretion from the close red dwarf companion. We have obtained extreme-ultraviolet (EUV) photometric and spectroscopic observations of EUVE J1016Ϫ053 with the Extreme Ultraviolet Explorer (EUVE). We report the discovery of a 230% EUV flux variation over a period of 57.3 minutes, which we attribute to surface abundance inhomogeneities modulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With the exception of a handful of hot white dwarfs in the close binary systems V471 Tauri (Jensen et al 1986), EUVE J1016[053 (Vennes et al 1997a), EUVE J0720[317 (Dobbie et al 1999), and the high-Ðeld magnetic white dwarf EUVE J0317[855 (Ferrario et al 1997), DA white dwarfs are generally not variable in the EUV. Its EUV variability and the fact that it has the largest known Si abundance measured in DA (Holberg, Barstow, & Sion 1998) gives an unique status to GD 394.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of a handful of hot white dwarfs in the close binary systems V471 Tauri (Jensen et al 1986), EUVE J1016[053 (Vennes et al 1997a), EUVE J0720[317 (Dobbie et al 1999), and the high-Ðeld magnetic white dwarf EUVE J0317[855 (Ferrario et al 1997), DA white dwarfs are generally not variable in the EUV. Its EUV variability and the fact that it has the largest known Si abundance measured in DA (Holberg, Barstow, & Sion 1998) gives an unique status to GD 394.…”
Section: Discussionmentioning
confidence: 99%
“…I should note at this point, however, that Vennes, Dupuis & Bowyer (1997) concluded that the accretion of a red dwarf stellar wind on to the white dwarf in the PCEB EUVE J1016−053 is much less efficient than that anticipated by their simple Bondi–Hoyle model. A similar conclusion was reached by Mullan et al (1991) for the PCEB V471 Tau.…”
Section: Feasibility Of the Wind Accretion Detection Mechanismmentioning
confidence: 87%
“…The presence of heavy elements in the atmospheres of the white dwarfs in EUVE J0720[317 and EUVE J1016[053 was inferred from a study of EUV E spectra of these objects (Dupuis, Vennes, & Bowyer 1997 ;Vennes et al 1997a), but the detection of photospheric carbon in GHRS spectra of these two objects and of EUVE J2013]400 is the Ðrst direct evidence for the presence of photospheric heavy elements. Figures 7 and 8 show a model atmosphere analysis of the helium and carbon abundance in the three white dwarfs.…”
Section: White Dwarf Composition : Abundance Of Helium and Carbonmentioning
confidence: 99%
“…On the other hand, Vennes et al (1997a) and Dupuis et al (1997) predicted an abundance of carbon of log C/H \ [ 6.2 and [5.7 in EUVE J1016[053 and EUVE J0720[317, respectively, based on a study of the EUV continuum spectral energy distribution. GHRS spectra centered on the C IV j1550 doublet were obtained at a single epoch for each star and reveal abundances of carbon larger than those inferred from EUV spectroscopy.…”
Section: White Dwarf Composition : Abundance Of Helium and Carbonmentioning
confidence: 99%
See 1 more Smart Citation